Dose Calculations for [131I] Meta-Iodobenzylguanidine-Induced Bystander Effects. Issue 1 (1st January 2014) - Gow, M. D.; Seymour, C. B.; Boyd, M.; Mairs, R. J.; Prestiwch, W. V.; Mothersill, C. E.
Targeted radiotherapy is a potentially useful treatment for some cancers and may be potentiated by bystander effects. However, without estimation of absorbed dose, it is difficult to compare the effects with conventional external radiation treatment. Methods: Using the Vynckier - Wambersie dose point kernel, a model for dose rate evaluation was created allowing for calculation of absorbed dose values to two cell lines transfected with the noradrenaline transporter (NAT) gene and treated with [ 131 I]MIBG. Results: The mean doses required to decrease surviving fractions of UVW/NAT and EJ138/NAT cells, which received medium from [ 131 I]MIBG-treated cells, to 25 – 30% were 1.6 and 1.7 Gy respectively. The maximum mean dose rates achieved during [ 131 I]MIBG treatment were 0.09 – 0.75 Gy/h for UVW/NAT and 0.07 – 0.78 Gy/h for EJ138/NAT. These were significantly lower than the external beam gamma radiation dose rate of 15 Gy/h. In the case of control lines which were incapable of [ 131 I]MIBG uptake the mean absorbed doses following radiopharmaceutical were 0.03 – 0.23 Gy for UVW and 0.03 – 0.32 Gy for EJ138. Conclusion: [ 131 I]MIBG treatment for ICCM production elicited a bystander dose-response profile similar to that generated by external beam gamma irradiation but with significantly greater cell death.